A method for preparing a fuel cell catalyst coating membrane scanning electron microscope sample
Through epoxy resin embedding, vacuuming, grinding and conductive treatment, the problem of bubbles and charge phenomena in the preparation of electron microscope samples of catalyst coated film is solved, and the observation quality and performance analysis capabilities of the samples are improved.
Patent Information
- Application Number
- CN202111336318.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-11-11
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2041-11-11
AI Technical Summary
There are bubbles and charge phenomena in the preparation of existing catalyst-coated film electron microscope samples, which interferes with the morphological analysis and defect analysis of the catalyst-coated film, making it difficult to effectively observe the performance of the catalyst-coated film.
After embedding the catalyst coating film with epoxy resin, vacuum treatment was performed, and then cured at 25°C to 50°C, followed by coarse grinding, fine grinding and polishing treatment, and finally conducting treatment, including carbon plating and copper patching to reduce bubbles and charge.
The prepared electron microscope sample has few bubbles and clean observation background, which can better observe and analyze the performance of the catalyst-coated film, effectively reduce the charge phenomenon, and improve the observation quality of the sample.
Smart Images

Figure HDA0003349410840000011 
Figure HDA0003349410840000012
Abstract
Description
Technical Field
[0001] The invention belongs to the field of electron microscope sample preparation, and in particular relates to a method for preparing a fuel cell catalyst coating membrane scanning electron microscope sample. Background Art
[0002] The catalyst coating membrane (CCM) is the core part of the fuel cell. It is composed of a proton exchange membrane and the cathode and anode catalyst coatings on both sides. Hydrogen forms hydrogen ions and electrons under the catalysis of the anode catalyst coating. The electrons reach the cathode through the external circuit, and the hydrogen ions reach the cathode through the proton exchange membrane. The oxygen in the cathode reacts with the electrons from the external circuit and the hydrogen ions from the proton exchange membrane to form water under the action of the cathode catalyst. The final product of hydrogen fuel cells is only water, and the reactants are air and hydrogen. Hydrogen can be obtained by electrolysis from the vast water resources. Therefore, hydrogen fuel cells are recognized as clean energy with great potential. Hydrogen fuel cells have the advantages of no noise, no pollution, and high efficiency. They are widely used in the automotive field, aerospace field, large power stations, etc.
[0003] Since the hydrogen fuel cell industry started late and the technology is not yet perfect, some minor problems are inevitable in the production process. This requires testing and characterization of the catalyst coating membrane, the core component of the fuel cell, to find the source of the problem and optimize its preparation process. Since the catalyst coating membrane is extremely thin, its thickness is in the micron range, and the catalyst coating membrane is relatively flexible, it is extremely difficult to prepare electron microscope samples.
[0004] The existing electron microscope samples of catalyst coating membranes are prepared by embedding CCM with epoxy resin, grinding and polishing after solidification. Since bubbles and charging are inevitably present in the preparation process of the electron microscope samples, the morphological analysis and defect analysis of the catalyst coating membrane are greatly interfered with. Therefore, how to eliminate the defects in the preparation process of the electron microscope samples of the catalyst coating membrane and purify the observation background of the catalyst coating membrane is of great significance for better observation of the catalyst coating membrane itself. Summary of the invention
[0005] The present invention aims to provide a method for preparing a fuel cell catalyst coating membrane scanning electron microscope sample. The prepared electron microscope sample has few bubbles, unobvious charging phenomenon, and a clean background, which is helpful for observing and analyzing the performance of the catalyst coating membrane itself.
[0006] Based on the above purpose, the technical solution adopted by the present invention is as follows:
[0007] The present invention provides a method for preparing a fuel cell catalyst coating membrane scanning electron microscope sample, comprising the following steps:
[0008] S1: After clamping both sides of the catalyst coating membrane by support clamps, vertically place it into a mold, add epoxy resin into the mold to embed the catalyst coating membrane, and perform vacuum treatment before the epoxy resin solidifies; cure the epoxy resin in the vacuum-treated mold at 25° C. to 50° C., and take out the sample embedded in the epoxy resin after curing from the mold for later use;
[0009] S2: coarsely grinding the sample embedded with the cured epoxy resin along the vertical surface of the catalyst coating film to expose the cross section of the catalyst coating film, and then fine grinding the exposed cross section;
[0010] S3: polishing the cross section of the finely ground catalyst coating membrane using a polishing agent;
[0011] S4: Conductively treat the cross section of the polished catalyst coating membrane to obtain a fuel cell catalyst coating membrane scanning electron microscope sample.
[0012] The present invention fixes the catalyst coating membrane with epoxy resin, and then performs coarse grinding, fine grinding, and polishing treatments in sequence, and then performs conductive treatment on the cross section of the catalyst coating membrane. This not only reduces bubbles in the electron microscope sample of the catalyst coating membrane and makes the observation background cleaner, but also effectively reduces the "charging phenomenon", making the electron microscope sample prepared by the method of the present invention more conducive to observing the properties of the catalyst coating membrane itself.
[0013] Furthermore, the epoxy resin includes epoxy resin crystal glue and epoxy resin curing agent; the weight ratio of the epoxy resin crystal glue to the epoxy resin curing agent is (2-3):1.
[0014] Furthermore, the epoxy resin includes epoxy resin crystal glue and epoxy resin curing agent; the weight ratio of the epoxy resin crystal glue to the epoxy resin curing agent is 2:1.
[0015] Experiments have shown that the curing rate is fastest when the weight ratio of epoxy resin crystal glue to epoxy resin curing agent is 2:1.
[0016] Furthermore, the vacuum treatment method is: place the mold with the epoxy resin embedded catalyst coating film in a vacuum environment of 0.1 MPa for 2 minutes, take it out and place it in the atmospheric environment until the bubbles on the surface of the epoxy resin disappear, and then place it in a vacuum environment of 0.1 MPa for 2 minutes.
[0017] The experiment found that the above two vacuum treatments can effectively reduce the amount of bubbles in the electron microscope sample and reduce the interference to the observation of the catalyst coating membrane.
[0018] Furthermore, the method of performing rough grinding and fine grinding on the sample embedded with the epoxy resin after curing in step S2 is as follows:
[0019] Using a grinding and polishing machine at a speed of 300 rpm / min, the sample was coarsely ground with 180-mesh sandpaper until the cross-section of the catalyst coating membrane was exposed, and then the exposed cross-section was finely ground with 300-400 mesh, 600-800 mesh, 1000-1200 mesh, 1500-2000 mesh, 3000-4000 mesh, and 5000 mesh sandpaper in sequence. The grinding time of each sandpaper was 20-80 seconds, and the grinding direction of the subsequent sandpaper was adjusted to 90° with the grinding direction of the previous sandpaper.
[0020] The above-mentioned polishing method can obtain a relatively good observation cross section of the catalyst coating membrane.
[0021] Furthermore, the polishing agent includes Al2O3 polishing liquid, SiO2 polishing liquid.
[0022] Experiments have found that the correct use of polishing agents can make the background of the scanning electron microscope image of the electron microscope sample cleaner, making it easier to observe the catalyst coating film.
[0023] Furthermore, the cross section of the catalyst coating membrane after polishing is subjected to conductive treatment as follows: the polished sample is left to stand for 24 hours to allow the polishing agent in the gaps in the cross section of the catalyst coating membrane to dry or vacuum treated to allow the polishing agent in the gaps in the cross section of the catalyst coating membrane to overflow; after cleaning and drying, the cross section of the catalyst coating membrane is subjected to carbon plating and copper glue pasting treatments in sequence.
[0024] If copper glue is applied to the surface of the sample alone, the electrons will be guided out only when the electron beam hits the copper glue. If other positions of the sample are observed, the "charging phenomenon" will still exist.
[0025] The present application performs carbon plating on the surface of the polished sample, which is equivalent to laying a continuous conductor "coat" on the sample. The electron beam can be well guided out at any position of the sample; but carbon plating is only to plate a thin conductive layer on the sample, and the speed of conductivity is limited. Therefore, if the electron microscope photograph is not scanned again for a long time after taking the electron microscope photograph, when the scanning is started again, the screen of the scanning electron microscope is very bright, but it will gradually return to normal. Therefore, carbon plating alone will cause a short-term "charging phenomenon"; and copper glue is applied to the surface of the carbon-plated sample, and the copper glue can quickly guide the electrons out, thereby effectively avoiding the "charging phenomenon".
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] The present invention uses epoxy resin to fix the catalyst coating film, and then performs coarse grinding and fine grinding in sequence to make the cross section of the catalyst coating film well presented, and then performs polishing treatment to make the electron microscope observation background of the catalyst coating film cleaner; then, carbon plating, copper glue pasting and other conductive treatments are performed in sequence, which can effectively avoid the "charging phenomenon" during electron microscope observation, so that the electron microscope sample of the present invention is more conducive to the observation and analysis of the performance of the catalyst coating film itself. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is the curing time diagram of AB glue with different weight ratios;
[0029] Figure 2 The curing time at different temperatures. DETAILED DESCRIPTION
[0030] To better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments. It should be understood by those skilled in the art that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0031] Unless otherwise specified, the test methods used in the examples are all conventional methods; the materials, reagents, etc. used, unless otherwise specified, can all be obtained from commercial sources. Among them, the aluminum oxide polishing liquid is 0.05CR, grade A; the silicon oxide polishing liquid is 0.06CR. The instruments used include a scanning electron microscope (model VEGA 3SBH, TESCAN, Czech Republic), a UNIPOL-830 metallographic grinding and polishing machine (Guangdong Metallographic Detection Technology Co., Ltd., with a magnetic disk), and a carbon coating machine (108C AutoCarbonCoater, Cressington Scientific Instrument Co., Ltd.).
[0032] Example
[0033] This embodiment provides a method for preparing a fuel cell catalyst coating membrane scanning electron microscope sample, comprising the following steps:
[0034] S1: Cut the catalyst coating membrane (CCM) into a rectangle (10mm*5mm), clamp the two long sides of the catalyst coating membrane with a support clamp, and vertically place it into a Goral blue sliced silicone mold (inner diameter 30mm*inner height 18mm), add epoxy resin to the mold to embed the catalyst coating membrane, and perform vacuum treatment before the epoxy resin solidifies; cure the epoxy resin in the vacuum-treated mold at 25℃~50℃, and take out the sample embedded in the epoxy resin after curing from the mold for use;
[0035] S2: coarsely grinding the sample embedded with the cured epoxy resin along the vertical surface of the catalyst coating film to expose the cross section of the catalyst coating film, and then fine grinding the exposed cross section;
[0036] S3: polishing the cross section of the finely ground catalyst coating membrane using a polishing agent;
[0037] S4: Conductively treat the cross section of the polished catalyst coating membrane to obtain a fuel cell catalyst coating membrane scanning electron microscope sample.
[0038] This embodiment will conduct a single factor analysis on the composition ratio of epoxy resin, vacuum treatment method, rough grinding, fine grinding method, polishing treatment and conductive treatment to obtain the best catalyst coating membrane electron microscope sample preparation conditions.
[0039] (I) Screening of epoxy resin component ratio
[0040] The epoxy resin is composed of epoxy resin crystal glue (glue A, LH0501) and epoxy resin curing agent (glue B, LH0502). The weight ratio of glue A to glue B is set to 4:1, 3:1, 2:1, 1:1, and 1:2, respectively. At room temperature, glue A and glue B are mixed and stirred according to the above ratio. At the beginning of the mixing, the two are turbid, and continue to stir until it becomes clear. Then continue to stir. The whole process lasts for 2 minutes. Then the mixed epoxy resin is poured into a Goral blue sliced silicone mold and allowed to stand. The curing state of the above samples is monitored respectively, and the curing time of the epoxy resin composed of glue AB with different weight ratios is counted. The results are as follows Figure 1 As shown in the figure, the numbers marked on the bar graph are the corresponding time. Figure 1 It can be seen that when the weight ratio of glue A to glue B is 2:1 or 3:1, the curing time is relatively short, especially when the weight ratio of glue A to glue B is 2:1, the curing time is significantly shortened, thereby significantly shortening the preparation time of electron microscope samples.
[0041] Based on the above analysis, the optimal weight ratio of glue A to glue B is 2:1.
[0042] (II) Screening of epoxy resin curing temperature
[0043] The epoxy resin with a weight ratio of 2:1 of glue A and glue B was used as the experimental object. The epoxy resin curing experiment was carried out at room temperature, 30℃, 40℃, 50℃, 60℃, 70℃, and 80℃ respectively. The curing time of the samples at different temperatures was counted. The results are as follows Figure 2As shown, it can be seen that at room temperature and within the temperature range of 50°C, the curing time is within 40 minutes, and the curing time is extended when the temperature rises. Therefore, the curing temperature can maintain a relatively short curing time at room temperature or within the range of 50°C. Since high temperature easily causes the bubbles in the epoxy resin to expand due to heat, the bubbles in the cured epoxy resin become larger and fixed, which is not conducive to the subsequent observation of the catalyst coating film.
[0044] Based on the above analysis, it is best to cure the epoxy resin at room temperature.
[0045] (III) Selection of vacuum treatment methods
[0046] The catalyst coating film is placed in an epoxy resin formed by mixing glue A and glue B in a weight ratio of 2:1, and vacuum treated at room temperature. The specific vacuum treatment methods are as follows:
[0047] Sample 1: no vacuum treatment;
[0048] Sample 2: Before placing the catalyst coating film in the epoxy resin, the epoxy resin was vacuum treated, specifically: the epoxy resin was placed under 0.1 MPa until bubbles floated to the surface;
[0049] Sample 3: The catalyst coating membrane was placed in epoxy resin and treated at 0.1 MPa for 0.5 min;
[0050] Sample 4: The catalyst coating membrane was placed in epoxy resin and treated at 0.1 MPa for 1 min;
[0051] Sample 5: The catalyst coating membrane was placed in epoxy resin and treated at 0.1 MPa for 2 min;
[0052] Sample 6: The catalyst coating membrane was placed in epoxy resin and treated at 0.1 MPa for 3 min;
[0053] Sample 7: The catalyst-coated membrane was placed in epoxy resin and treated at 0.1 MPa for 6 min;
[0054] Sample 8: After the catalyst coating membrane was placed in epoxy resin, it was treated at 0.1 MPa for 2 minutes, placed in a normal pressure atmosphere until the bubbles on the surface of the epoxy resin disappeared, and then treated again at 0.1 MPa for 2 minutes.
[0055] After the epoxy resin in the above sample is cured, the bubbles after curing are observed under a scanning electron microscope. The results show that even after a vacuum treatment of up to 6 minutes, there are still bubbles around the CCM, and bubbles are more likely to appear at the location where the catalyst coating membrane is peeled off and near the contact between the CCM and the support clip. This is because the space at the above location is small, the epoxy resin is relatively viscous, and the surface tension is large. When embedding the sample, the epoxy resin is not easy to enter the gap of such small space, making it easy for bubbles to exist in such space positions, and there are obstacles around the bubbles to prevent the bubbles from floating and moving. If a single vacuum treatment is used, there will be a lot of bubbles accumulated on the surface of the epoxy resin, and the effect of continuing to vacuumize will be poor due to the obstruction of this layer of bubbles; while the double vacuum treatment method is used, after the first vacuum treatment, it is placed in a normal pressure environment, so that the bubbles on the surface of the epoxy resin disappear, and the vacuum treatment is performed again, which can better extract the bubbles in the epoxy resin.
[0056] Based on the above analysis, choosing at least two vacuum treatments and placing the resin in a normal pressure environment after each vacuum treatment is more conducive to removing bubbles from the epoxy resin.
[0057] (IV) Selection of grinding and polishing treatment methods
[0058] The epoxy resin with a weight ratio of 2:1 of A glue and B glue was used as the experimental object. After the above-mentioned two vacuum treatments and room temperature curing, a CCM glue sample was formed, and rough grinding and fine grinding were performed.
[0059] 1. The influence of the number of sandpaper on the grinding effect
[0060] The first set of sandpaper polishing: Set the grinding and polishing machine speed to 350rpm, and polish the cured CCM glue sample in turn with sandpapers with mesh sizes of P180, P300, P600, P1000, P1500, P3000 and P5000. After each piece of sandpaper is polished for 40s, rotate 90° in the same direction and then polish with the next piece of sandpaper. Press the sample slightly during polishing. The sandpaper with mesh size of P180 needs to be polished until the CCM sample is exposed.
[0061] The second set of sandpaper polishing: Set the grinding and polishing machine speed to 350rpm, and polish the cured CCM glue sample with sandpapers of mesh numbers P180, P400, P800, P1200, P2000, and P4000 in turn. After each piece of sandpaper is polished for 40s, rotate 90° in the same direction and then polish with the next piece of sandpaper. Press the sample slightly during polishing. The sandpaper with mesh number P180 needs to be polished until the CCM sample is exposed.
[0062] It can be seen from the SEM images of the samples after polishing with the two different sandpapers that the scanning electron microscope images after polishing with the two sets of sandpapers are similar, which means that the polishing is gradually carried out from sandpaper with large mesh to sandpaper with small mesh, and the mesh difference of the sandpaper for early polishing is small, and the mesh size of the sandpaper for later polishing is large enough, so the final scanning electron microscope image effect will not be too bad.
[0063] 2. The influence of the speed of the grinding and polishing machine on the grinding effect
[0064] Referring to the grinding method of the first set of sandpaper mentioned above, the rotation speed of the grinding and polishing machine is adjusted to 300rpm / min, 400rpm / min, and 500rpm / min respectively. From the SEM images of the samples after grinding at the three different rotation speeds, it can be seen that the SEM image of the sample after grinding at the lowest rotation speed of 300rpm / min is the best. This is because when the rotation speed is high, the tangential force of the sandpaper is relatively large. On the basis of grinding the sample direction every 10 seconds, the same position of the sample will be polished more times with greater force, especially the scratches of the sandpaper will be deeper after several hours, which is equivalent to indirectly extending the grinding time; if the sample can be rotated for grinding at a high rotation speed, this situation can be avoided, and the grinding time can even be appropriately reduced, but when grinding at a high rotation speed, the sample will be subjected to a large traction force, and it will be difficult to fix the sample by manual grinding, and it is extremely difficult to operate the sample continuously.
[0065] In summary, choosing a grinding speed of 300rpm / min not only makes manual grinding easy, but also has a good grinding effect.
[0066] 3. The influence of each sandpaper grinding time on the grinding effect
[0067] Referring to the grinding method of the first set of sandpapers mentioned above, except for the first sandpaper P180 which needs to grind the CCM glue sample until the CCM sample is exposed, the grinding time of the other sandpapers is 20s, 60s or 80s. It can be seen from the SEM images of the samples after grinding with different grinding times that the longer the grinding time, the better the SEM image effect. Considering the time cost and the SEM image effect, the best grinding method is to grind each sandpaper for 60s.
[0068] 4. The influence of the grinding direction of each sandpaper on the grinding effect
[0069] Referring to the grinding method of the first set of sandpaper mentioned above, the samples were respectively ground without rotating and with self-rotating in the same direction. From the SEM images of the samples after grinding in the above two methods, it can be seen that the effect of grinding by rotating the sample 90° in the same direction or by self-rotating is better.
[0070] 5. The influence of polishing treatment on the scanning electron microscope effect
[0071] After the first set of sandpaper grinding is completed, Al2O3 polishing liquid and SiO2 polishing liquid are used in turn for 1 minute of polishing; at the same time, the samples without polishing are used as a comparison. From the SEM images of the polished and unpolished samples, it can be seen that the SEM image effect after polishing is significantly better than that without polishing.
[0072] (V) Screening of different conductive treatment methods
[0073] The samples after the above-mentioned most preferred grinding and polishing treatment were subjected to the conductive method screening test, and the specific test methods included the following four types: A. No conductive treatment; B. Only conductive copper glue treatment without carbon plating; C. Only carbon coating conductive treatment without conductive copper glue; D. Conductive copper glue treatment after carbon coating conductive treatment. It can be seen from the electron microscope effect diagrams of the above four samples that the scanning electron microscope images of the samples without carbon plating and copper glue and copper glue without carbon plating are particularly poor, the pictures are relatively bright, and the traces of the samples being burned and deformed by the electron beam emitted by the scanning electron microscope can be seen. This is because the epoxy resin has no conductivity and cannot guide the electrons out, so that the electrons accumulate in large quantities on the surface of the sample, thereby generating a "charge phenomenon". The copper glue will only guide the electrons out when the electron beam is shot on the copper glue. If other positions of the sample are observed, the "charge phenomenon" will also occur. After the sample is carbon-plated, it is equivalent to laying a continuous conductor "jacket" on the sample. The electron beam can guide the electrons out well at any position of the sample, thereby avoiding the "charge phenomenon".
[0074] The difference between carbon plating with copper glue and carbon plating without copper glue in different conductive treatment experiments: First, the electrons in the electron beam emitted from the scanning electron microscope can only be guided out through the stage in the vacuum chamber of the scanning electron microscope after hitting the surface of the sample, while carbon plating only coats a thin conductive layer on the sample, and the speed of conduction is limited. Therefore, if the scan is not performed again for a long time after taking a photo, the screen of the scanning electron microscope will be very bright when scanning is started again, but it will gradually return to normal. Although this is only a short-term "charging phenomenon", it will also delay some time. This situation will not occur after applying conductive copper glue on the basis of carbon plating, because copper glue can quickly guide electrons out. Therefore, applying copper glue after carbon plating can effectively avoid the "charging phenomenon".
[0075] In summary, the preferred parameters in the preparation method of the fuel cell catalyst coating membrane scanning electron microscope sample of the present invention are as follows: AB glue weight ratio 2:1; vacuum treatment at a vacuum degree of 0.1MPa, vacuum treatment 2 times, 2min / time; room temperature curing; grinder speed of 300rpm / min; use 7 sandpapers from small to large meshes for slightly hard grinding, except for the first sandpaper with the smallest mesh number which is polished until the sample is exposed, the other sandpapers are each polished for 60s, and it is optimal to rotate the sample 90° after the same time and then polish it during each sandpaper grinding; using Al2O3 polishing agent and SiO2 polishing agent can make the scanning electron microscope image background of the sample better; carbon plating and conductive copper glue on the sample after grinding can effectively avoid the "charging phenomenon".
[0076] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing a fuel cell catalyst coating membrane scanning electron microscope sample, characterized in that: The steps include: S1: After clamping both sides of the catalyst coating membrane by support clamps, vertically place it into a mold, add epoxy resin into the mold to embed the catalyst coating membrane, and perform vacuum treatment before the epoxy resin solidifies; cure the epoxy resin in the vacuum-treated mold at 25° C. to 50° C., and take out the sample embedded in the epoxy resin after curing from the mold for later use; S2: coarsely grinding the sample embedded with the cured epoxy resin along the vertical surface of the catalyst coating film to expose the cross section of the catalyst coating film, and then fine grinding the exposed cross section; S3: polishing the cross section of the finely ground catalyst coating membrane using a polishing agent; S4: conducting a conductive treatment on the cross section of the polished catalyst coating membrane to obtain a scanning electron microscope sample of the fuel cell catalyst coating membrane; The vacuum treatment method is as follows: placing the mold with the epoxy resin embedded catalyst coating film in a vacuum environment of 0.1 MPa for 2 minutes, taking it out and placing it in an atmospheric environment until the bubbles on the surface of the epoxy resin disappear, and then placing it in a vacuum environment of 0.1 MPa for 2 minutes; The method of performing rough grinding and fine grinding on the sample embedded with the epoxy resin after curing in step S2 is as follows: Using a grinding and polishing machine at a speed of 300 rpm / min, the sample was coarsely ground with 180-mesh sandpaper until the cross-section of the catalyst coating membrane was exposed, and then the exposed cross-section was finely ground with 300-400 mesh, 600-800 mesh, 1000-1200 mesh, 1500-2000 mesh, 3000-4000 mesh, and 5000 mesh sandpaper in sequence. The grinding time of each sandpaper was 20-80 seconds, and the grinding direction of the subsequent sandpaper was adjusted to 90° with the grinding direction of the previous sandpaper.
2. The preparation method according to claim 1, characterized in that: The epoxy resin includes epoxy resin crystal glue and epoxy resin curing agent; the weight ratio of the epoxy resin crystal glue to the epoxy resin curing agent is (2-3):
1.
3. The preparation method according to claim 2, characterized in that: The weight ratio of the epoxy resin crystal glue to the epoxy resin curing agent is 2:
1.
4. The preparation method according to claim 1, characterized in that: The polishing agent includes Al2O3 polishing liquid and SiO2 polishing liquid.
5. The preparation method according to claim 1, characterized in that: The conductive treatment of the cross section of the catalyst coating membrane after polishing is specifically as follows: the polished sample is left to stand for 24 hours to allow the polishing agent in the gaps in the cross section of the catalyst coating membrane to dry or vacuum treated to allow the polishing agent in the gaps in the cross section of the catalyst coating membrane to overflow; after cleaning and drying, the cross section of the catalyst coating membrane is subjected to carbon plating and copper glue pasting treatments in sequence.
Citation Information
Patent Citations
Scanning electron microscope sample preparation method for observing the internal structure of ion spraying composite powder
CN112485279A
Method for characterizing surface residual stress of thermal barrier coating caused by grinding process
CN113252718A